2020
DOI: 10.1111/1756-185x.13998
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the relationship between the pelvic floor and sexual dysfunction in women with Sjögren’s syndrome

Abstract: Sjögren's syndrome (SS) is a chronic, systemic, autoimmune disease characterized by lymphocytic infiltration of all exocrine glands, especially tear and salivary glands. 1 Typical symptoms of SS are dry eyes, mouth and vagina but other mucosa can also be involved, resulting in a disturbing sicca syndrome that can impair quality of life. 2 As in other autoimmune diseases, SS predominantly affects women more than men and may occur in patients of all ages but typically has onset in the 4th to 6th decades of life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…Regarding the representativity of the sample, the proportion of UI types was similar than those previously reported in young women [ 4 ]. The values of PF distress and impact of the current sample were lower when compared to previous research in women with PF disorders and healthy women [ 45 , 46 ], probably because the current sample was not in treatment or seeking treatment for PF or continence at the time of the study, and also due to the young age of the sample. Furthermore, no women reported pain or any discomfort throughout the assessments, demonstrating the safety and repeatability of the protocol.…”
Section: Discussioncontrasting
confidence: 79%
“…Regarding the representativity of the sample, the proportion of UI types was similar than those previously reported in young women [ 4 ]. The values of PF distress and impact of the current sample were lower when compared to previous research in women with PF disorders and healthy women [ 45 , 46 ], probably because the current sample was not in treatment or seeking treatment for PF or continence at the time of the study, and also due to the young age of the sample. Furthermore, no women reported pain or any discomfort throughout the assessments, demonstrating the safety and repeatability of the protocol.…”
Section: Discussioncontrasting
confidence: 79%
“…Studies demonstrated that women with SS had pelvic floor problems 7,10 . PFDI‐20 is generally used for pelvic floor disorders 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this was explained as the antibodies in SS negatively affect gastrointestinal smooth muscle, parasympathetic function, and detrusor activity 8,9 . In a recent study, it was revealed that sexual dysfunction and pelvic floor problems are associated with women with pSS 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation